Dietary calories and lipids synergistically shape adipose tissue cellularity during postnatal growth - Meln, Irina; Augustin, Hellmut (Molecular metabolism, 2019)
Objective - The susceptibility to abdominal obesity and the metabolic syndrome is determined to a substantial extent during childhood and adolescence, when key adipose tissue characteristics are established. Although the general impact of postnatal nutrition is well known, it is not clear how specific dietary components drive adipose tissue growth and how this relates to the risk of metabolic dysfunction in adulthood. - Methods - Adipose tissue growth including cell proliferation was analyzed in juvenile mice upon dietary manipulation with in vivo nucleotide labeling. The proliferative response of progenitors to specific fatty acids was assayed in primary cultures. Long-term metabolic consequences were assessed through transient dietary manipulation post-weaning with a second obesogenic challenge in adulthood. - Results - Dietary lipids stimulated adipose tissue progenitor cell proliferation in juvenile mice independently of excess caloric intake and calorie-dependent adipocyte hypertrophy. Excess calories increased mitogenic IGF-1 levels systemically, whereas palmitoleic acid was able to enhance the sensitivity of progenitors to IGF-1, resulting in synergistic stimulation of proliferation. Early transient consumption of excess lipids promoted hyperplastic adipose tissue expansion in response to a second dietary challenge in adulthood and this correlated with abdominal obesity and hyperinsulinemia. - Conclusions - Dietary lipids and calories differentially and synergistically drive adipose tissue proliferative growth and the programming of the metabolic syndrome in childhood.
Gesehen am 30.10.2019
Available online 5 April 2019